2012
DOI: 10.1111/j.1095-8649.2012.03265.x
|View full text |Cite
|
Sign up to set email alerts
|

A review of the application of molecular genetics for fisheries management and conservation of sharks and rays

Abstract: Since the first investigation 25 years ago, the application of genetic tools to address ecological and evolutionary questions in elasmobranch studies has greatly expanded. Major developments in genetic theory as well as in the availability, cost effectiveness and resolution of genetic markers were instrumental for particularly rapid progress over the last 10 years. Genetic studies of elasmobranchs are of direct importance and have application to fisheries management and conservation issues such as the definiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
208
0
7

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 212 publications
(216 citation statements)
references
References 300 publications
(501 reference statements)
1
208
0
7
Order By: Relevance
“…The reasons for this are less clear, although metabolic rate has been suggested as the most likely correlate for slow molecular rates in elasmobranchs (Martin, 1999). Estimates of the number of nucleotide substitutions per site per year (S s À1 y À1 ) in elasmobranchs vary between 0.7 Â 10 À09 and 1.15 Â 10 À08 (reviewed by Dudgeon et al, 2012), which is approximately an order of magnitude slower than rates found in mammals. Our estimate of an average rate of S s À1 y À1 in mobulids of 8.82 Â 10 À09 (95% HPD: 7.15 Â 10 À09 À 10.77 Â 10 À09 ) falls within the range estimated for elasmobranchs.…”
Section: The Molecular Clock Age Estimates and The Fossil Recordmentioning
confidence: 99%
“…The reasons for this are less clear, although metabolic rate has been suggested as the most likely correlate for slow molecular rates in elasmobranchs (Martin, 1999). Estimates of the number of nucleotide substitutions per site per year (S s À1 y À1 ) in elasmobranchs vary between 0.7 Â 10 À09 and 1.15 Â 10 À08 (reviewed by Dudgeon et al, 2012), which is approximately an order of magnitude slower than rates found in mammals. Our estimate of an average rate of S s À1 y À1 in mobulids of 8.82 Â 10 À09 (95% HPD: 7.15 Â 10 À09 À 10.77 Â 10 À09 ) falls within the range estimated for elasmobranchs.…”
Section: The Molecular Clock Age Estimates and The Fossil Recordmentioning
confidence: 99%
“…These sites are separated by a 2,000-m deep channel, which suggests movements of individuals between subpopulations might be restricted by bathymetric features and/or regional circulation . The possibility exists, however, that geographically adjacent subpopulations to the present study area have a degree of connectivity, and this should be assessed through analysis of manta ray image databases from different localities, such as waters off Fiji, New Caledonia and western Australia, and by the application of molecular genetics approaches (e.g., Dudgeon et al 2012;Kashiwagi et al 2012).…”
Section: Photo-id Validationmentioning
confidence: 99%
“…However, a recent study refuted this, indicating a greater estimated population size in the eastern Pacific (Burgess et al 2014), while historic abundance trends in the western North Atlantic suggest recovering populations (Curtis et al 2014). Nonetheless, genetic analysis of Australian white shark populations suggests estimates of contemporary effective population sizes approach levels at which adaptive potential may be lost (Blower et al 2012). A similar concern was expressed following the observation that several contemporary white sharks sampled from across the Mediterranean all had the same Pacific clade mitochondrial haplotype (Gubili et al 2011).…”
Section: Introductionmentioning
confidence: 73%
“…Population genetic analysis has been useful for shark management and conservation efforts (Dudgeon et al 2012). However, the veracity of population and demographic parameters estimated from analysis of DNA sequences depends to a large degree on sampling a reasonable number of individuals.…”
Section: Introductionmentioning
confidence: 99%